Suitability and Economics of Baco Skyline Crane - Sethi, Y. R.; Sood, K. G. (Indian Forester, 1977)
Off-road transportation in Log-form is very expensive and time consuming under present conventional methods in the country, Due to the inefficiency of these methods we are forced to switch over to the modern logging practices in the interest of better timber harvesting at low logging costs. With a view to achieve this end long distance Skyline Cranes have recently been introduced in some of the hill states of the country. In order to find out the efficiency, usefulness and economics of the Skyline Cranes when used under Indian conditions, it is essential to carry out a "Time and Cost Study", before such a costly imported equipment is recommended for Off-road transportation on large scale. The present study has revealed that with the help of a Baco Long Diatance Skyline Crane we could transport about 4000 m3 of timber in log-form at an average cost of Rs. 27.63 per m3 per span, in one year. The introduction of such an equipment will reduce the off-road transportation cost and also avoid hand-sawing or timber at stump site which involves lot of wastage.